Strengthening Digital Marketing for Young Entrepreneurs at Wiraraja Mart, Sumenep Regency - Mohammad Firlie Pranata; Norsain (Jurnal Pengabdian Masyarakat Bestari, 2022)
The digital era is a challenge and opportunity in doing business, these challenges and opportunities need to be answered with skills that are honed according to developments. Online stores are becoming increasingly popular among many groups, in fact, almost all people who don't have shops in general also sell online. This is because it is considered easy and practical. This development must also be followed by Wiraraja Mart, Sumenep Regency. At an early age and still not taking advantage of sales in the online world due to limited human resources, efforts have been made to find a solution with young entrepreneurs. The young cooperatives consist of wiraraja students and youth youth who lack knowledge and still have no experience selling online. To overcome this, it is necessary to have related training and assistance about becoming a digital marketer. This service program is expected to be the first step in starting an online business at Wiraraja Mart through young cooperatives, they are required to have a creative and innovative mentality.